Conventional medical therapy in heart failure patients eligible for the PARADIGM-HF, DAPA-HF, and SHIFT trials. (15th July 2022) - Shoji, Satoshi; Kohsaka, Shun; Shiraishi, Yasuyuki; Kohno, Takashi; Sawano, Mitsuaki; Ikemura, Nobuhiro; Niimi, Nozomi; Nagatomo, Yuji; Tanaka, Toshikazu D.; Takei, Makoto; Ono, Tomohiko; Sakamoto, Munehisa; et al.
Abstract: Background: Recent trials on novel heart failure (HF) treatments (angiotensin receptor-neprilysin inhibitor, sodium-glucose cotransporter 2 inhibitor, and ivabradine) emphasize the use of conventional medical therapy (angiotensin-converting enzyme inhibitors, beta-blockers [BB], and mineral corticosteroid receptor antagonists). We aimed to evaluate the prescription rate of conventional medical therapy and its association with long-term outcomes in patients eligible for recent trials. Methods: We examined 1295 consecutive patients with HF with reduced ejection fraction (HFrEF) from a multicenter registry (WET-HF registry). We assessed conventional medical therapy implementation among patients meeting the PARADIGM-HF/DAPA-HF and SHIFT enrollment criteria. We also examined the association between conventional medical therapy use and long-term outcomes within each enrollment criterion. Results: Overall, 62.2% and 35.3% of HFrEF patients met the enrollment criteria of the PARADIGM-HF/DAPA-HF and SHIFT trials. Only 33.9% and 31.9% received full conventional medical therapy within each patient subset. Notably, 84.2% of patients who met the SHIFT enrollment criteria were on BB, and only 23.0% and 4.4% were on ≥50% or the full recommended dose, respectively. Implementation of full conventional medical therapy use was associated with lower 2-year mortality and HF readmission rates in the PARADIGM-HF/ DAPA-HF eligible group (HR 0.68, 95% CI 0.50–0.92). The use of BB at ≥50% of the recommended dose was associated with lower 2-year mortality and HF readmission rates in the SHIFT-eligible group (HR 0.50, 95% CI 0.30–0.84). Conclusions: Conventional medical therapy was underutilized among patients eligible for novel trials within a Japanese HF registry. Further efforts to optimize conventional medical therapy are needed. Highlights: Recent novel heart failure (HF) trials recommended the use of conventional medical therapy in the enrollment criteria. 62.2% and 35.3% of the patients met the enrollment criteria of the PARADIGM-HF/DAPA-HF and the SHIFT trials. conventional medical therapy was underutilized (~30%) among patients eligible for novel HF trials. Use of conventional medical therapy was associated with lower rates of 2-year mortality and HF readmission. Optimizing conventional medical therapy remains a crucial step in improving the outcomes of HF patients.